The Forum of Federations Handbook of Fiscal Federalism (Springer Nature, 2023)
This open access handbook compares fiscal federalism arrangements in eleven federal/ decentralized countries. Each chapter examines an individual country, laying out its constitutional design as relates to fiscal powers and the division of those powers between levels of government. Specifically, the analyses consider powers of taxation, spending, regulation, and more. Focusing on Australia, Brazil, Canada, Ethiopia, Germany, India, Italy, South Africa, Spain, Switzerland, and the United States, the contributors provide a fascinating account of how federal countries are confronting the traditional challenges of conflicts over division of fiscal powers while also coping with the ongoing challenges of globalization and citizen empowerment that arise from the information revolution. As a companion to the Forum of Federations Handbook of Federal Countries 2020, this volume considers how relationships and roles in different orders of government are being reshaped, and shows how local solutions inspired by global principles help strengthen government accountability and improve citizens’ quality of life. This is an open access book.